ORGANIC WASTE TO ENERGY IN LATIN AMERICA AND THE CARIBBEAN (LAC); STATE-OF-THE-ART LITERATURE REVIEW - Silva-Martinez, Rodolfo Daniel [UNESP]; Sanches-Pereira, Alessandro; Persson, M.; Scarlat, N.; Grassi, A.; Helm, P. (Eta-florence Renewable Energies, 2018)
Organic waste to energy (OWtE) technologies have been already developed and implemented in Latin America and the Caribbean (LAC) countries, but are still far away to significantly contribute not only to manage and treat the ever-increasing waste volumes in the region but also to supply its energy demand and meet national GHG reduction goals. The technical complexity of these technologies, dearth of research, high investment costs and political deficiencies have not allowed for an appropriate implementation of relevant OWtE in the region, where the applicability of large-scale treatment plants remains to be demonstrated. This research presents the state-of-the art of OWtE technologies in the context of LAC countries' based on archival research method. The main findings show that OWtE have the potential to improve waste management and energy systems in the region by reducing environmental impacts, along with a series of social and economic benefits, such as increasing sustainable energy supply. However, there is still a lack of investment and participation of stakeholders aligned with other challenges, which inhibit the implementation and diffusion of OWtE in LAC.
Keywords: organic waste; bioenergy; thermochemical conversion; biochemical; Latin America; Caribbean